No Longer ‘Ali-Baba’ But ‘Ali Chandran’ Businesses in Brunei Darussalam: An Exploration - Li Li Pang (Policy & Governance Review, 2019)
The issue of ‘Ali Baba’ businesses, specifically in the retail sector, has been long debated in Brunei Darussalam, socially and recently in the legislature. The definition of ‘Ali Baba’ business in Brunei Darussalam refers to expatriates use of citizens’ licence to conduct a business in the country. Although such practices are well-known and widely written in Malaysia and to a lesser extent in Indonesia, there is scarce academic literature of the phenomenon in Brunei Darussalam. This paper is a preliminary attempt to fill in the literature gap and to find out the extent and characteristics of ‘Ali Baba’ businesses in Brunei Darussalam, specifically in the retail sector. Semi-structured interviews were used to obtain empirical data as well as from personal on-site observations in a small Mukim or sub-district in Brunei Darussalam. The preliminary findings of the research were profound. This paper argues that the term ‘Ali Baba’ businesses is no longer suitable to refer the retail sector in Brunei Darussalam, rather, it should be known as ‘Ali Chandran’ businesses, as the expatriate partner is now commonly from the Asian sub-continent.